Effects of the Rehabilitation Therapy for Persons with Amphetamine use disorder by BasicBuddhist Teaching of Ethic “Ruk-Nuea-Ruk” (Six Saraniya-Dhamma) with Five Percepts of Adolescents Who have treatment for Amphetamine use Disorder on the Knowledge of Substance Abuse and the Level of Self-defense Intentions for Relapse Prevention of Substance Abuse - Nitayawan, Sirirat; Thongseaw, Natedao; Nantarat, Preechaya; Aroonlueng, Aukarachi (Journal of The Royal Thai Army Nurses, 2024)
This quasi-experimental research investigates the effects of the BasicBuddhist Teaching of Ethic “RukNuea-Ruk” (Six Saraniya-Dhamma) with Five Percepts, on substance knowledge and self-defense intentions for relapse prevention of substance abuse. The study involved 54 male juveniles convicted of amphetamine or methamphetamine offenses, housed at a juvenile training and rehabilitation center. The participants were divided into two groups: a control group of 27 participants and an experimental group of 27 participants. Data were analyzed using One-Way ANOVA and Independent t-tests to determine differences between groups. The results indicated that the experimental group demonstrated significantly higher levels of drug knowledge and self-defense intentions after the intervention and three months later compared to their levels before the intervention and compared to the control group (p ≤ .05). Therefore, it can be concluded that the “Ruk-Nuea-Ruk” program effectively enhances substance knowledge and self-defense intentions among adolescents previously involved with amphetamines. Early implementation of this rehabilitation program can help reduce the social issues associated with amphetamines.